Recent advances of atomically thin 2D heterostructures in sensing applications. (October 2021) - Li, Zhong; Yao, Zhengjun; Haidry, Azhar Ali; Luan, Yange; Chen, Yongli; Zhang, Bao Yue; Xu, Kai; Deng, Ruixiang; Duc Hoa, Nguyen; Zhou, Jintang; Ou, Jian Zhen
Highlights: The synthesis approaches of atomically-thin two-dimensional heterostructures are summarized. The fundamental and unique features of two-dimensional heterostructures for physical and chemical sensing are discussed. The recent progress of two-dimensional heterostructures based photodetectors is reviewed. The current development of gas and biological sensors enabled by two-dimensional heterostructures is revealed. Graphical Abstract: ga1 Abstract: The emerging two-dimensional (2D) materials have led to the revolution across many fields in optics, electronics, optoelectronics, and sensors. Physical sensors such as photodetector and chemical sensors like gas and biological sensors play important roles in optical communications, imaging, environmental monitoring, remediation, as well as healthcare and medical industries. The implementation of 2D materials can significantly enhance the performances of such sensors due to their ultra-thin planar surface, large surface-to-volume ratio, and unique physiochemical properties. Peculiar features such as tunable band structures and relatively large charge carrier mobilities in certain 2D materials further provide additional dimensions to realize high-performance sensors from optical, electronic, and optoelectronic transducing platforms. Enabled by the weak van der Waals (vdW) force, individual 2D materials can be artificially stacked to realize the atomically thin 2D heterostructures, producing unprecedented features which are not accessible in the individual 2D counterparts or other low-dimensional heterostructures. Here, the atomically thin 2D heterostructures are comprehensively reviewed by firstly summarizing their controllable and scalable synthesis. Meanwhile, the band structure alignment and interfacial charge transfer behavior of 2D heterostructures are specifically introduced and their influences on physical and chemical sensing are revealed. In addition, the state-of-the-art progress is reported and critically discussed. Finally, the current challenges and prospects of 2D heterostructure-based sensors are provided.